Pengaruh Model Pembelajaran Cooperative Integrated Reading And Composition (Circ) Terhadap Motivasi Belajar Pak Dan Budi Pekerti Siswa Kelas XI SMA Swasta HKBP 2 Tarutung Tahun Pembelajaran 2022/2023 - Putri Laura Srivani Manalu; Tiurma Berasa; Goklas J. Manalu; Maryska Silalahi; Sabar Rudi Sitompul; Dorlan Naibaho (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
The aim of this research is to determine the effect of the cooperative integrated reading and composition learning model on learning motivation for Christian Religious Education & Character Education in class XI of HKBP 2 Tarutung Private High School for the 2023/2024 Academic Year.This research uses a Posttest-Only Control type experimental method. The population is all class XI of HKBP 2 Tarutung Private High School for the 2023/2024 academic year, totaling 160 people. The sample was determined using a technique taken deliberately (purposive sampling) with the specified conditions that the learning material being experimented with was in that class, namely class XI IIS-1 students totaling 32 people as the experimental class and XI IIS-3 totaling 32 people as the control class. The research instrument used a 27 item test. The t test used is the Separated Variance t test according to the test analysis requirements, namely n1=n2 and the variance of the two sample groups is homogeneous. The results of hypothesis testing obtained a value of tcount= 13.9 > ttable (=0.05; dk=n1+n2-2=62) = ttable 1.669, so H0 is rejected and H1 is accepted. This research concludes that students' motivation to learn Christian Religion & Character Education taught using the cooperative integrated reading and composition learning model is higher than that taught using the conventional learning model in class XI of HKBP 2 Tarutung Private High School for the 2023/2024 Academic Year.